Pengaruh Kebijakan Hutang dan Net Profit Margin Terhadap Devidend Payout Ratio Pada PT. Lippo Karawaci Tbk - Nurul Rizkania; Nurhayati Nurhayati (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
This study aims to determine the effect of debt policy and net profit margin on the dividend payout ratio at PT. Lippo Karawaci Tbk. The population in this study began from 1996 until 2018 or for 23 years. While the samples in this study were from 2011 to 2018 or for 8 years with a sample technique that was purposive sampling. Source of data used in the form of secondary data, namely the financial statements of PT. Lippo Karawaci, Tbk. Data analysis techniques used are Debt to Equity analysis, Net Profit Margin, and Devidend Payout Ratio, multiple linear regression analysis, multiple correlation coefficient, determination coefficient, by testing the hypothesis of the classic assumption test, and partial t test. The results showed that the debt policy partially had no significant effect on the Dividend Payout Ratio, the Net Profit Margin partially affected and significantly on the Dividend Payout Ratio, the debt policy and the Net Profit margin had no effect and had no significant effect on the Devidend Payuot Ratio.